HUBUNGAN INDEKS MASSA TUBUH DENGAN KADAR HIGH SENSITIVITY C-REACTIVE PROTEIN SERUM PADA MAHASISWA OBES DAN TIDAK OBES DI FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI MANADO - Rattu, Christy; Bolang, Alexander S. L.; Kawengian, Shirley E. S. (e-Biomedik, 2013)
Abstract: The increasing of Metabolic syndrome become a problem nowadays. The prevalence of metabolic symbol can be confirmed tend to increase with the increasing of obesity prevalence. The indicator to measure body’s fat is Body Mass Index (BMI). For obesity patient, their adiposity system produce duce protein messenger that cause inflamation. The level of High Sensitivity C-Reactive Protein (hsCRP) is one of the parameter that used to detect inflamation process. This research is conducted with the purpose to know the difference of hsCRP level between Obese students and Non-Obese students in Medical Faculty, to know the relation between BMI and hsCRP level between Obese and Non-Obese students in Medical Faculty. This is an analitic research with cross sectional approach that used 59 sample that consists of 30 Man and 29 woman, with the age range between 18-22 years old. The result of this research shown that there is a big difference of hsCRP level between obese and non-obese students. Cobclusion: There is a meaningful positif relationship between BMI with hsCRP level for obese students, and there is no meaningful relationship between BMI with hsCRP level for the non-obese students in Medical Faculty. Keywords: BMI, hsCRP, obesity Abstrak: Meningkatnya sindroma metabolik menjadi masalah sekarang ini. Prevalensi sindroma metabolik dapat dipastikan cenderung meningkat dengan meningkatnya prevalensi obesitas. Indikator untuk mengukur lemak tubuh adalah indeks massa tubuh (IMT). Pada penderita obesitas, jaringan adiposity menghasilkan protein-protein duta yang menyebabkan adanya inflamasi. Kadar High Sensitivity C-Reactive Protein (hsCRP) merupakan salah satu parameter uji yang dipakai untuk mendeteksi proses inflamasi. Penelitian ini telah dilakukan dengan tujuan untuk mengetahui perbedaan kadar hsCRP pada mahasiswa obes dan non-obes di Fakultas Kedokteran, untuk mengetahui hubungan antara IMT dengan kadar hsCRP pada mahasiswa obes dan non-obes di Fakultas Kedokteran. Penelitian ini bersifat analitik dengan pendekatan cross sectional menggunakan 59 sampel yang terdiri 30 laki-laki dan 29 wanita, berusia 18-22 tahun. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang bermakna kadar hsCRP pada mahasiswa obes dan non-obes. Simpulan: Ada hubungan positif yang bermakna antara IMT dengan kadar hsCRP pada mahasiswa obes, dan tidak terdapat hubungan yang bermakna antara IMT dengan kadar hsCRP pada mahasiswa non-obes di Fakultas Kedokteran. Kata kunci: IMT, hsCRP, obesitas.